Microcirculatory effects of sildenafil in experimental testicular torsion in rats - Oroszi Márton (WORLD JOURNAL OF UROLOGY, 2018)
Purpose: Investigate the short-term effect of sildenafil on microcirculation, especially the velocity, the pattern of the flow and the recruitment of the leukocyte in postcapillaries. Methods: In male Sprague–Dawley rats, the microcirculatory consequences of 60 min experimental testicular torsion, followed by 240 min of reperfusion, were examined. Using fluorescence intravital microscopy, changes in red blood cell velocity in post-capillary venules and rolling as well as adhesion of leukocytes in the postcapillary venules were examined before the torsion and every hour during the reperfusion period. Sildenafil was given 10 min prior to reperfusion (iv 0.7 mg/kg, n = 6), while control animals received saline vehicle (n = 5). Results: The characteristic flow motion disappeared in the affected testicular during the torsion. Red blood cell velocity values were dramatically decreased (by > 50%) and both rolling and adhesion of leukocytes increased during the reperfusion phase. Sildenafil treatment resulted in significantly higher red blood cell velocity values during the entire reperfusion period, but exerted only a temporary positive effect on the plost-ischaemic leukocyte–endothelial interactions. Conclusions: Intraoperative administration of sildenafil during surgical detorsion may provide marked testicular microperfusion benefits, but failed to influence the overall leukocyte-driven microcirculatory inflammatory reactions. © 2018 Springer-Verlag GmbH Germany, part of Springer Nature